Anisotropy characteristics of coal shrinkage/swelling and its impact on coal permeability evolution with CO2 injection. Issue 5 (6th October 2016) - Liu, Shimin; Wang, Yi; Harpalani, Satya
Abstract: Coal deforms with gas depletion during coal bed methane (CBM) primary recovery and CO2 storage for purposes of sequestration or enhanced recovery. The sorption‐induced deformation associated with gas adsorption and desorption has been experimentally and theoretically studied and is considered to be a unique feature of coal. The results of a series of experimental measurements of coal deformation with gas injection and depletion using helium, methane, CO2, and various mixtures of methane and CO2 revealed that the coal sorption‐induced deformation exhibits anisotropy, with larger deformation in direction perpendicular to bedding than those parallel to the bedding planes. Furthermore, the deformation of coal is reversible for helium and methane with injection/depletion, but not for CO2 . Aiming at improving the understanding of enhanced CBM process, a coal deformation experimental study on methane displacement with CO2 was performed as well, where incremental swelling was measured for each CO2 displacement step. The total induced swelling strain (1.68%) with CO2 saturation was less than that for pure CO2 injection‐induced strain (1.87%) at same pressure of 5.9 MPa (850 psi). The measured deformation with CO2 injection was applied to a constant‐volume based analytical coal permeability model, which is capable of accommodating the anisotropic sorption‐induced deformation. Based on the modeling results, it was found that application of isotropic deformation in permeability model can overestimate the permeability loss compared to anisotropic deformation. This demonstrates that the anisotropic coal deformation should be considered to predict the permeability behavior of CBM as well as CO2 sequestration/ECBM projects. © 2016 Society of Chemical Industry and John Wiley & Sons, Ltd